2006
DOI: 10.1016/j.ijrobp.2006.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adaptive optimization: Selective boosting of high-risk tumor subvolumes

Abstract: Background and purpose-A tumor subvolume-based, risk-adaptive optimization strategy is presented.Methods and materials-Risk-adaptive optimization employs a biological objective function instead of an objective function based on physical dose constraints. Using this biological objective function, TCP is maximized for different tumor risk regions while at the same time minimizing NTCP for organs at risk (OAR). The feasibility of risk-adaptive optimization was investigated for a variety of tumor subvolume geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Ref. 5 for the details), utilize a prescription of 39 fx / 2 Gy to 98% PTV, which is based on the IMRT dose prescription used in Ref. [21].…”
Section: Imrt Treatment Planning For Four Different Selective Boostinmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. 5 for the details), utilize a prescription of 39 fx / 2 Gy to 98% PTV, which is based on the IMRT dose prescription used in Ref. [21].…”
Section: Imrt Treatment Planning For Four Different Selective Boostinmentioning
confidence: 99%
“…Currently, the integration of biological information into radiotherapy (RT) treatment planning with the aim of boosting high-risk tumor subvolumes is of great interest [1][2][3][4][5][6][7][8] -this concept has been termed either 'selective boosting' [4][5][6] or 'dose painting' [7][8]. To achieve selective boosting IMRT based on patient-specific biological information, the following techniques and methods have to be available: a highly conformal RT delivery technique, a method to decide on the boosting level, and a functional or molecular imaging modality having high imaging accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The anticipated toxicity would be reduced because the volumes receiving very high radiation doses would be significantly smaller. 7 The success of a focal dose escalation strategy would depend on the accurate detection of these biologically radioresistant regions. This could be achieved with functional imaging techniques, such as fluorine-18-fluorodeoxyglucose-positron emission tomography ( 18 F-FDG-PET).…”
Section: Introductionmentioning
confidence: 99%
“…Specific biomarker probes can be administered and visualized in vivo with the aid of functional imaging modalities such as PET. In addition, it has been suggested that the efficacy of radiation treatment may be increased considerably by creating and delivering heterogeneous dose distributions based on PET data (1)(2)(3). However, until now, only phase I dose escalation trials based on 18 F-FDG imaging have been conducted (4,5).…”
mentioning
confidence: 99%